After UCS: Workplace Occupation in Britain in the 1970s. Issue 1 (1st April 2021) - Tuckman, Alan
Abstract : This paper traces the development of this form of industrial action through the 1970s, the emergence of an alternative economic voice, ultimately almost silenced in the 1980s with the dominance of neo-liberalism, leaving a sedimental alternative which periodically reappears. We first need to consider the context for this occupation movement and the social, political and economic developments of the post-war period which facilitated this form of resistance. Then we consider the nature of 'occupation', the forms it takes, and what differentiates it from strikes and other manifestations of organized conflict arising from the employment of labour power under capitalism, before examining the pattern of occupation after UCS. We indicate that the movement left a sediment of ideas and practices, not just in terms of 'occupation' itself as a form of industrial action, but also of an alternative economy rooted in workers' self-management and socially useful production.